(untitled) (Journal of Parents and Teachers, 2014)
About 50 years ago the introduction of television in Spain and since then, our lives have changed a lot. Currently, we are immersed in television culture, and because of this, the article offers guidelines for watching TV, general ideas about the power that television has and encourages children to start viewing it always accompanied by their families and Seeing contents appropriate to their age.